List of Trade Unionists & Labour Party Members [International Brigade]
1937 034-0192-014 12. E.McBride TGWU (Docks Section) Greenock Branch. Dependant: W. Mackie NUGMW Kirkcaldy No.9 Shop Steward. Dependant: Mrs. W. Mackie, 38 Mid St., Kirkcaldy, (£1-10-0) J. McGee NAFTA Leeds - Organiser. Dependant: W. McAuley NUS Glasgow Dependant: Mrs. McAuley, 50 Cavendish St., Glasgow C.5 (£1-5-0). C. McCormick Fife Miners Glencraig Branch Dependant: Mrs. McCormack, McMenemy's Bldgs., Glencraig, Fife. (£1-0-0) Ethel Murphy (Medical Unit) Islington L.P. Dependant: A. Porter NUDAW Equity Branch Dependant: Ada Philps Medical Unit. Nat. Union of County Officers Hertford. Dependant: V. Shammah NUC Manchester General Branch Dependant: *S. Stanley East Islington DLP Dependant: [D. Springhall NUC London Br.] [Dependant: Mrs M. Springhall, c/o L.A.I. 53 Greys Inn Rd., W.C.1 (£1-0-0)] J. Tunnah Post Office Workers Edinburgh Br. Steward. Dependant: T. Thomas SWMF Taff Merthyr Dependant: R. Ward SAWU Birmingham Dependant: *F. Whitehead LP Withenshaw Vice Pres. NUDAW Manchester Central. Dependant: E. Wilson NUGMW Bromley East Branch Dependant: Mrs. Wilson, 19 Aberfeldy St., Poplar, E.14. ( £2-10-0). 292/946/34/193(xii)